PENGARUH KINERJA PELAYANAN DAN POTONGAN HARGA TERHADAP LOYALITAS KONSUMEN ( STUDY KASUS SIMPLY FRESH LONDRY – PEKANBARU) - Efendi, Rahmat; Sutrisna, Endang (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
This research was conducted with the aim to find out the Effect of Service Performance and Price Pieces on Consumer Loyalty (Case Study on Simply Fresh Laundry- Pekanbaru). This study uses quantitative research and a sample of 92 respondents who are consumers of simply fresh laundry - pekanbaru. Data collection methods used in this study were questionnaires with purposive sampling technique. The results showed that service performance variables directly influence the price discount variable, the price discount variable directly influences the consumer loyalty variable, the service performance variable has a direct effect on consumer loyalty, and the service performance variable has an indirect effect on consumer loyalty variables. Keywords: Service Performance, Price Discounts and Consumer Loyalty.